A MODEL OF A MOBILE ANDROID APPLICATION FOR ENVIRONMENTAL PATIENT MONITORING - Surtel, Wojciech; Maciejewski, Marcin; Cieślar, Michał (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
To use a smart phone as a part of a telemedical health monitoring system requires a dedicated application running under control of the device’s operating system. This article contains the project and functional requirements of such an application. It should provide necessary functionality by means of a simple user interface for the patient under monitoring and be able to collect, store, process and send the data to the database application running on the central server. It must perform necessary measurements of life parameters and calculate location in appropriate time periods while still maintaining data synchronization with the central server. It must also be able to limit battery use in the portable device. It is also necessary to implement forced communication mechanism in cases of sudden health risks and patient deterioration.